Novel Optics-Based Approaches for Cardiac Electrophysiology: A Review - Müllenbroich, M. Caroline; Kelly, Allen; Acker, Corey; Bub, Gil; Bruegmann, Tobias; Di Bona, Anna; Entcheva, Emilia; Ferrantini, Cecilia; Kohl, Peter; Lehnart, Stephan E.; Mongillo, Marco; Parmeggiani, Camilla; et al. (Frontiers in Physiology, 2021)
Optical techniques for recording and manipulating cellular electrophysiology have advanced rapidly in just a few decades. These developments offer analysis of cardiac cellular dynamics at multiple scales while largely overcoming the drawbacks associated with solid state electrodes. The recent advent of optogenetics opens up new possibilities for regional and tissue-level electrophysiological control and may hold promise for future novel clinical applications. This article reviews the state-of-the-art optical techniques used for cardiac electrophysiological research and the underlying biophysics. The design and performance of optical voltage reporters and optogenetic tools are reviewed along with the limitations of current probes. The physics of light interaction with cardiac tissue is detailed and the challenges presented to the use of optical sensors and actuators. Case studies include the use of fluorescence recovery after photobleaching and super-resolution microscopy to explore the micro-structure of cardiac cells and a review of two photon and light sheet technologies applied to cardiac tissue. The emergence of cardiac optogenetics is reviewed and the current work exploring the potential clinical use of optogenetics in implantable defibrillators is also described. Approaches which combine optogenetics and optical voltage measurement are discussed, in terms of platforms that allow the real-time manipulation of whole heart electrophysiology in open and closed-loop systems to study optimal ways to terminate spiral arrhythmias. The design and operation of optics-based approaches that allow high-throughput cardiac electrophysiological assays will be discussed. Finally, the emerging techniques of photo-acoustic imaging and stress sensors are described along and the strategies for future development and establishment of these techniques in mainstream electrophysiological research.